O tempo e o museu: manifestações da modernidade, pós-modernidade e hipermodernidade no Museu de Arte do Rio Grande do Sul Ado Malagoli 1957-2009 - Isaacsson, Gisela Brum (2011)
This work analyses characteristic points of three moments of culture: Modernity, Post-Modernity and Hypermodernity. It is understood the existence of these periods due to the predominance and repetition of certain behaviors in the social life of the 19 th , 20 th and early 21 st centuries, enabling the authors used to build the bibliography in this work to use such nomenclature. However, it is necessary to keep two aspects in mind: time is continuous and does not admit intersections; and the behaviors in each moment are not tight and the only verifiable ones in that time. Based on this, the study highlights, in each of the three moments, the most frequent attitudes mentioned in several books, as able to bring special characterization as well as a differentiated definition. After that, it verifies the relation between these moments and the formation and development of Rio Grande do Sul Ado Malagoli Museum of Art, electing three dates: the year of its official opening in 1957, pointing out characteristics from Modernity; the year it was moved to the building at Alfândega Square in 1978, highlighting traits of Post-Modernity; and the year of the exposition Art in France 1860-1960: The Realism , in 2009, stressing aspects of Hypermodernity. The crossing of the selected dates, by simple sampling, and characteristics of each of the periods previously mentioned are dealt with in the study, showing how social behaviors towards the museum may reflect characteristics of the chosen moments of culture. In order to develop the theme, the concept of social memory coined by Maurice Halbwachs is used along with an analysis of photographies, news reports, documents, interviews, exposition catalogues and attending sheets, and bibliography review which support the proposed analysis